Coping with grief when someone you love dies suddenly - Williams, Mary ([Huddersfield] Sudden, 2011)
This book is for people who have suffered the shattering experience of a loved one dying suddenly. It aims to help understand the emotions and feelings commonly suffered. It provides straightforward advice on how to cope and who can help you to recover.
UCWS-3318g & UCWS-3319g donated by Prof. Eric Julian Manalastas - November 2016
Keywords: Bereavement; Loss (Psychology); Grief Therapy